Harnessing geothermal energy from produced water in the Neuquén basin through Organic Rankine Cycle application - Vela Garcia, Julián Agustín (2023)
The decarbonization of the energy sector is a major global challenge, requiring the transformation and improvement of energy production systems to reduce greenhouse gas emissions. The hydrocarbon industry offers a potential pathway for transition, as many productive hydrocarbon deposits with a high water cut are increasing over time. The geothermal energy contained in the co-produced water, which is transported to the surface by pumping, can be harnessed for a wide range of applications, depending on the temperature of the extracted fluid. The use of the energy contained in produced water is considered one of the most promising proposals for extending the economic life of hydrocarbon reservoirs with low enthalpy geothermal resources, characterized by temperatures below 90 °C. This is facilitated by the existing infrastructure in the fields, which enables the installation of heat extraction equipment, thereby reducing the high costs associated with the drilling and completion stages of the wells and eliminating the related risks. This work aims to evaluate the potential for generating electrical energy using an “Organic Rankine Cycle” (ORC) system from the heat contained in the produced water of Bandurria Centro and Bajo del Toro Norte hydrocarbon reservoirs, situated on the Eastern Flank of the Neuquén Basin. According to the results, the produced water temperatures in the aforementioned areas are deemed suitable for the application of an ORC system, enabling the transfer of thermal energy to generate electricity and thus be used within the field. Maximum power outputs of up to 6.611 kW were observed for produced water temperature of 62.55 °C with an ambient temperature of 5.5 °C. However, the extreme ambient temperatures of 39 °C made it impossible for the ideal ORC system to remain operational. Therefore, the use of energy contained in the produced water through the implementation of an ORC system is a promising approach for extending the economic life of hydrocarbon deposits and contributing to decarbonization efforts.